Green Energy Products and The Relationship of The Customer’s Consideration for The Environment and Perceived Risk Involved with The Mediating Position of Customer Purchasing Intentions - Omar Jawabreh; Al Fahmawee , Emad Al Dein; Al-Rawashdeh, Osama Mohammad; Alrowwad, Ala’aldin; Alrjoub, Ashraf (International Journal of Energy Economics and Policy, 2022)
The goal of this study is to examine green energy goods and the relationship of the consumer concern for the atmosphere and perceived danger associated with the mediating role of the customer buying intentions; the point of view of international tourists in Jordan. The sampling technique was accompanied by a cross-sectional, quantitative, and explanatory design, whereby 340 individuals were chosen using a random population method reflecting the tourists of the Jordan for a two-week span beginning on 11/11/2020. By circulation of a paper questionnaire and with the aid of some tourist guides, the person sample was achieved. Moreover, through two stages, the structural model was being analyzed. In the first stage (direct effect) the effect (PK-appropriate CPI) was not important, so H1 was not sponsored. However, the result was important with regard to (PK ΔPR), and hypothesis 2a was supported. (PK ΔEC) were not significant, so hypothesis 2a was not supported. Furthermore, the direct impact of product danger and environmental problems on purchasing intentions were explored, resulting in negative/positive and important findings (PR over CPI, P < 0.05; and environmental concerns over purchase intentions, P > 0.05), so H3awere was endorsed, however, H3b was not supported.